The IoT for Visualization of RC Circuits Transient Phenomena - Al Faris Habibullah; Nanang Suwondo (The Indonesian Institute of Science and Technology Research, 2022)
The development of a device for visualizing the transient phenomena of RC circuits on smartphones has been carried out, utilizing the IoT platform of NodeMCU as a solution to restrictions on attendance in laboratory during COVID-19 pandemic. The quantity displayed is the voltage and electric current during charging or discharging capacitor. NodeMCU is coupled with a CD4066 to switch the process, and a 74HC4051 multiplexer to select the voltage or current value of capacitor. At the end there is an RC circuit connected to the switch and the multiplexer and also a voltage source. User commands are sent from the smartphone to the NodeMCU via the Blynk server. The software consists of a program uploaded in NodeMCU and a Blynk graphic interface arranged on smartphone. The system can work quite well, including controlling the charging and discharging capacitor. The visual appearance of voltage and current on smartphone screen quite similar with those of theory.